2017
DOI: 10.3390/ijms18122683
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of sEH Inhibitors on the Proliferation and Migration of Vascular Smooth Muscle Cells

Abstract: Epoxyeicosatrienoic acid (EET) is a cardioprotective metabolite of arachidonic acid. It is known that soluble epoxide hydrolase (sEH) is involved in the metabolic degradation of EET. The abnormal proliferation and migration of vascular smooth muscle cells (VSMCs) play important roles in the pathogenesis of atherosclerosis and restenosis. Thus, the present study investigated the effects of the sEH inhibitor 12-(((tricyclo(3.3.1.13,7)dec-1-ylamino)carbonyl)amino)-dodecanoic acid (AUDA) on platelet-derived growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…However, since only using chemical inhibitor without specific knockdown of sEH, it could not fully rule out the effects of the complete sEH protein on the process of vascular calcification. In fact, several studies have reported that the effect of sEH inhibitors could be different from genetic knockout of sEH [ 16 ]. For example, despite many studies that had shown that genetic deletion of sEH decreased the pathogenicity of several diseases, both Li et al [ 17 ] and Hutchens et al [ 18 ] reported that deficiency of sEH in mice exacerbates cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…However, since only using chemical inhibitor without specific knockdown of sEH, it could not fully rule out the effects of the complete sEH protein on the process of vascular calcification. In fact, several studies have reported that the effect of sEH inhibitors could be different from genetic knockout of sEH [ 16 ]. For example, despite many studies that had shown that genetic deletion of sEH decreased the pathogenicity of several diseases, both Li et al [ 17 ] and Hutchens et al [ 18 ] reported that deficiency of sEH in mice exacerbates cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of a specific biosynthetic arachidonic acid pathway could alter the metabolic flux resulting in side effects (Sonnweber et al, 2018). Interactions and changes in metabolic flux have been determined for COX-2 and sEH inhibitors (Kim et al, 2017). PTUPB is a dual acting molecule and that concurrently inhibits sEH and COX-2 resulting in potent kidney protective effects while reducing side effects (Hye Khan et al, 2016;Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Vascular beneficial therapeutic actions for sEH inhibitors extends to atherosclerosis and vascular remodeling (Fleming, 2001; Imig, 2012; Imig & Hammock, 2009). Vascular smooth muscle cell culture experiments have ascertained that sEH inhibitors decrease proliferation and migration (Davis et al, 2002; Fleming, 2001; Kim et al, 2017). Acute vascular inflammation in mice is attenuated by increased endothelial cell EET levels or sEH inhibition (Deng et al, 2011).…”
Section: Soluble Epoxide Hydrolase Inhibitorsmentioning
confidence: 99%